2007
DOI: 10.1111/j.1365-2648.2007.04460.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses and Internet health information: a questionnaire survey

Abstract: The development of nursing competencies in accessing and using online resources is a key precursor to supporting patients and families' use of the medium. Access to Internet resources at work, along with training and time for searching, is necessary for the development of skills enabling effective use of information technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…As the details of the professionals e38 British Journal of General Practice, January 2015 There are studies that suggest face-toface training is comparable with online training, 6,7,22,23 although many indicate that the computer platforms need to be improved as participants encountered difficulty using them. 24,25 Nevertheless, most studies found an increase in knowledge and satisfaction when approaching the problems dealt with in the training courses. 9 Educational courses, independently of the technique used, improve control of hypertension, dyslipidaemia, and diabetes, as well as behaviour, particularly concerning the prevention of events in patients with a high cardiovascular risk.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…As the details of the professionals e38 British Journal of General Practice, January 2015 There are studies that suggest face-toface training is comparable with online training, 6,7,22,23 although many indicate that the computer platforms need to be improved as participants encountered difficulty using them. 24,25 Nevertheless, most studies found an increase in knowledge and satisfaction when approaching the problems dealt with in the training courses. 9 Educational courses, independently of the technique used, improve control of hypertension, dyslipidaemia, and diabetes, as well as behaviour, particularly concerning the prevention of events in patients with a high cardiovascular risk.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Johnson 12 examined the significant difference (P < 0.002 using a two-tailed unpaired t-test) and describe that online preparation for high-stakes examinations could improve student performance in medical microbiology. Gilmour, et al, 13 found that most respondents had internet access at home to improve the practice and to expressed the quality of online information. Scott, et al, 14 investigated the e-learning asthma resource was a useful supplement to the paediatric asthma lecture and workshop that helpful to improve clinical practice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the worksite, lack of time, combined with lack of library access and database or computer access are obstacles (Bertulis, 2008;Dee & Stanley, 2005;Gilmour, Scott, & Huntington, 2008;Lawton, Montgomery, & Farmer, 2001;Tanner et al, 2004). Lack of competency in searching, inadequate computer technology skills, and lack of interest are individual challenges (Estabrooks, O'Leary, Ricker, & Humphrey, 2003;Spenceley, O'Leary, Chizawsky, Ross, & Estabrooks, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%